Mixed use housing-storage and detriment of public space in Barrios Altos. Case study: Five corners - Luna Cruz, Ruth (2021)
This article seeks to make known of the high-risk that Barrios Altos has of losing its built heritage due to the presence of disproportionate storages. At the start, this article point out public projects and research results in Barrios Altos. In addition, there are two referential cases in Latin America: Quito and Old Havana. Finally, the research shows the study of how the mixed use of housing-storage sway in the low quality of public space in the Cinco Esquinas sector, Barrios Altos. The Space Syntax- Depthmap program is used for the analysis. Besides the following variables are considered: permeability, vehicular traffic, visual perception, storages, visual wealth, identity and activities in the public space. As a colophon, the article makes know the municipal control management and the need to have immediate legal processesare for the protection of the historic district.